2020
DOI: 10.1016/j.jaut.2019.102332
|View full text |Cite
|
Sign up to set email alerts
|

Epstein Barr virus nuclear antigen 1 (EBNA-1) peptides recognized by adult multiple sclerosis patient sera induce neurologic symptoms in a murine model

Abstract: Multiple sclerosis (MS) is an autoimmune demyelinating disease with progressive neurodegeneration and complex etiology likely involving genetic and environmental factors. MS has been associated with Epstein Barr virus (EBV) infection, with patients often showing enhanced responses to EBV antigens. To determine whether abnormal EBV nuclear antigen-1 (EBNA-1) humoral immunity can serve as an initiator of autoimmune responses in MS, we investigated the fine specificities of the humoral immune response against EBN… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
50
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
3
1

Relationship

0
10

Authors

Journals

citations
Cited by 63 publications
(52 citation statements)
references
References 45 publications
2
50
0
Order By: Relevance
“…Very interesting results come from a recent study showing that MS patient sera, differently from healthy controls, recognize unique EB nuclear antigen (EBNA) 411-426 epitopes with antibodies cross-reacting with myelin basic protein (MBP). Moreover SJL/J and Balb/c mice injected with EBNA 411-426 peptide develop signs of EAE [78]. Based on these findings, a new line of investigation can be developed for a further insight into the possible role of EBV through molecular mimicry in MS pathogenesis.…”
Section: Epstein-barr Virus (Ebv)mentioning
confidence: 99%
“…Very interesting results come from a recent study showing that MS patient sera, differently from healthy controls, recognize unique EB nuclear antigen (EBNA) 411-426 epitopes with antibodies cross-reacting with myelin basic protein (MBP). Moreover SJL/J and Balb/c mice injected with EBNA 411-426 peptide develop signs of EAE [78]. Based on these findings, a new line of investigation can be developed for a further insight into the possible role of EBV through molecular mimicry in MS pathogenesis.…”
Section: Epstein-barr Virus (Ebv)mentioning
confidence: 99%
“…Libbey et al [ 70 ] hypothesize that MS could be triggered via molecular mimicry, whereby specific peptides secreted by pathogens have sequence or structural similarities to self-antigens. Previous studies have suggested the role of molecular mimicry in the pathogenesis of MS through Haemophilus influenzae viral infections [ 71 ], and a potentially similar mechanism has been observed for EBV infection [ 72 ]. The proposed cascade of events leading to CNS autoimmunity following EBV infection involves the proliferation and maturation of T-cells against Epstein–-Barr virus nuclear antigen 1 (EBNA1) [ 73 ].…”
Section: Immune Activation: What Is the Motive For The Crime?mentioning
confidence: 87%
“…Several of these antigens have structural or sequence similarities with epitopes of bacterial and viral antigens. Thus, molecular mimicry is an appealing hypothesis for the origin of autoreactivities, with EBV and human herpes virus 6 proposed as viral candidates that mimic myelin proteins (27,46,47). New bacterial candidates have been identified as molecular mimics relevant to MS from in-depth studies of the microbiome (48).…”
Section: Discussionmentioning
confidence: 99%